Changes in Pupil Area during Low-energy Femtosecond Laser-assisted Cataract Surgery. - Mirshahi, Alireza; Ponto, Katharina A. (Journal of Ophthalmic & Vision Research)
Purpose: To study the potential changes in pupil area within low-energy femtosecond-laser assisted cataract surgery (FLACS). Methods: A retrospective assessment of the pupil size was performed in the eyes undergoing FLACS using the Ziemer LDV Z8. We measured the pupil diameters as part of the images taken preoperatively and at the completion of laser pretreatment (after releasing the suction). We calculated the pupil area in 40 eyes of 40 patients (14 right and 26 left eyes). The mean ±standard deviation (SD) of age of the patients was 74 ±7.4 years (range: 51-87). Paired t-test was used for statistical analyses. Subgroups were built with reference to age and preoperative pupil area (smaller than or equal to the median versus larger than the median). Results: The mean ± SD axial length, anterior chamber depth, white-to-white distance and lens thickness were 24.01 ±1.47, 3.23 ±0.4, 11.97 ±0.49, and 4.59 ±0.41 mm, respectively. The mean ±SD pupil area was 39.33 ± 7.1 mm² preoperatively and 39.3 ± 6.75 mm² after laser pretreatment. The mean ± SD change in pupil area was -0.03 ±2.12 mm². There were no statistically significant changes between preoperative and post-laser pupil areas (P = 0.93, 95% CI: -0.71 to 0.65). Comparisons within subgroups also did not detect pupil area reduction. Conclusion: This study did not detect statistically significant changes in pupil area after laser pretreatment using low-energy FLACS. This observation is in contrast to previous studies using other laser platforms.